2021
DOI: 10.5604/01.3001.0014.9280
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional habits and emotional eating of adults during social isolation days due to Covid-19 pandemic

Abstract: Purpose: In this study, the effect of BMI values on eating habits and emotional eating of individuals in social isolation and quarantine process implemented in Turkey as a result of COVID-19 pandemic were investigated. Materials and methods: An online questionnaire was used in this cross-sectional study. A total of 2019 participants were included in the study between April and May 2020. Individuals' nutritional behaviors, emotional eating scores using the three-factor eating questionnaire stress level, appetit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A total of 35 studies examined the relationship between FEDs and domains of psychosocial distress during the COVID-19 outbreak (e.g., depression, anxiety, and post-traumatic stress symptoms) ( Table 3 ). Specifically, five studies assessed COVID-related distress [ 53 , 84 , 85 , 86 , 87 ], whereas the majority assessed different domains of psychological distress in a short time lag (last 24 h or the “past week”), during the COVID-19 restrictions [ 50 , 76 , 83 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ]. These psychopathological outcomes were grouped in the same meta-analysis because of the low number of studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 35 studies examined the relationship between FEDs and domains of psychosocial distress during the COVID-19 outbreak (e.g., depression, anxiety, and post-traumatic stress symptoms) ( Table 3 ). Specifically, five studies assessed COVID-related distress [ 53 , 84 , 85 , 86 , 87 ], whereas the majority assessed different domains of psychological distress in a short time lag (last 24 h or the “past week”), during the COVID-19 restrictions [ 50 , 76 , 83 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ]. These psychopathological outcomes were grouped in the same meta-analysis because of the low number of studies.…”
Section: Resultsmentioning
confidence: 99%
“…These psychopathological outcomes were grouped in the same metaanalysis because of the low number of studies. Evidence of positive correlation with psychosocial distress was found for weight gain (r = 0.28, 95% CI = 0.11-0.44) [52,53,76,86,87,89,91,99,104,105], body image concerns (r = 0.20, 95% CI = 0.00-0.40) [50,100,101], overeating (r = 0.36, 95% CI = 0.08-0.06), and emotional eating (r = 0.30, 95% CI = 0.22-0.38) [36,[85][86][87][88]90,93,[96][97][98]100,102,103]. The analyses suggested that many effect sizes were highly heterogeneous (I 2 range 89.07 to 99.08%, see Table 3).…”
Section: Correlates Of Ed Symptomsmentioning
confidence: 99%
“…Madalı et al [38] confirmed that during the COVID-19 pandemic, a higher frequency of emotional eating was observed in the sub-group of obese adult participants of the study than in normal weight and underweight ones. Yılmaz et al [39] observed that during the COVID-19 pandemic, emotional eating increased in direct proportion with increasing BMI, and involuntary weight gain in an adult population. McAtamney et al [40] indicated that adult respondents who were characterized by emotional eating behaviors increasing during the COVID-19 pandemic simultaneously demonstrated increasing depression levels.…”
Section: Discussionmentioning
confidence: 99%